Humanized Mouse Models for the Advancement of Innate Lymphoid Cell-Based Cancer Immunotherapies - Horowitz, Nina B.; Mohammad, Imran; Moreno-Nieves, Uriel Y.; Koliesnik, Ievgen; Tran, Quan; Sunwoo, John B. (Frontiers in Immunology, 2021)
Innate lymphoid cells (ILCs) are a branch of the immune system that consists of diverse circulating and tissue-resident cells, which carry out functions including homeostasis and antitumor immunity. The development and behavior of human natural killer (NK) cells and other ILCs in the context of cancer is still incompletely understood. Since NK cells and Group 1 and 2 ILCs are known to be important for mediating antitumor immune responses, a clearer understanding of these processes is critical for improving cancer treatments and understanding tumor immunology as a whole. Unfortunately, there are some major differences in ILC differentiation and effector function pathways between humans and mice. To this end, mice bearing patient-derived xenografts or human cell line-derived tumors alongside human genes or human immune cells represent an excellent tool for studying these pathways in vivo. Recent advancements in humanized mice enable unparalleled insights into complex tumor-ILC interactions. In this review, we discuss ILC behavior in the context of cancer, the humanized mouse models that are most commonly employed in cancer research and their optimization for studying ILCs, current approaches to manipulating human ILCs for antitumor activity, and the relative utility of various mouse models for the development and assessment of these ILC-related immunotherapies.